ANALISIS MANAJEMEN KOMPETENSI PEDAGOGIK GURU DI YAYASAN SANTO STANISLAUS BORONG - Hera, Raimundus Mera; Widiatna, Alexius Dwi (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2023)
This research aims to explain the implementation of pedagogical competency management in the teaching and learning process of teachers at Yayasan Santo Stanislaus Borong. This qualitative study employs in-depth interviews, document analysis, and observations involving five informants: the Foundation Chair, Kindergarten Principal, Elementary School Principal, Junior High School Principal, and Senior High School Principal within Yayasan Santo Stanislaus Borong, East Manggarai Regency, NTT. The findings indicate that the management of pedagogical competencies in the teaching and learning process is well-organized, supported by several factors including collaboration among teachers, effective communication between teachers and students, and support from parents, as well as the professionalism and quality of the teachers.